Antibacterial activity of nano goldparticles synthesized by Bacillus Sps. - Biradar, Diva; Lingappa, K; Dayanand, A (Journal of Ecobiotechnology, 2012)
The synthesis and bioactivity of gold nanoparticles has been extensively studied. However, the antibacterial activity of gold nano particles individually or in combination with different antibiotics has not been demonstrated. In the present study the effect of gold nano particles on the antibacterial activity of different antibiotics was evaluated against Staphylococcus aureus, k.pnemonea, P.aureginosa, E.coli. Disk diffusion method was used to determine the antibacterial activity of various antibiotics in the absence and presence of sub inhibitory concentration of gold nano particles. A clinical isolates of S. aureus, k.pnemonea, p.aureginosa,E.coli. were used as the test strains. In the presence of sub-inhibitory concentration of gold nano particles the antibacterial activities of all antibiotics have . Increased from minimum 2 mm to a maximum of 8 mm. The highest increase was observed for ceftazidime followed by genthamycin. These results signify that the gold nano particles potentiate the antimicrobial action of cephalosporins and amino glycosides, suggesting a possible utilization of nano compounds in combination therapy against S. aureus, k.pnemonea, p.aureginosa,E.coli.